PENTINGNYA UPAYA MENINGKATKAN MINAT BELAJAR IPS DENGAN MENGGUNAKAN MEDIA AUDIOVISUAL PADA SISWA SD KELAS RENDAH DI SD NEGERI KUNIR 1 DEMPET DEMAK - Fadia Nurluthfiana; Erlita Umi Masytoh; Silvia Berliana; Wafna Jannata Ulya (Universitas Palangka Raya, 2023)
The purpose of this study was to determine the extent to which learning activities using audio-visual media increased interest in learning social studies. Local facts show that when learning social studies, students are more concerned with themselves, do not pay attention to the teacher and are indifferent to other friends. This shows that students' interest in IPS is still low. Audio-visual media is expected to increase interest in learning Social Sciences because the application of audio-visual media can increase. So that the character of students can change habits and care for the environment. The research method uses quantitative research methods, which are carried out by looking for material in written form. The purpose of this research is to increase interest in learning social studies through audiovisual media. The results of this study indicate that the use of audiovisual media is very important to increase elementary school students' interest in social studies learning.